2016
DOI: 10.1007/s10681-016-1651-0
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for late leaf spot and rust resistance using an improved genetic map and extensive phenotypic data on a recombinant inbred line population in peanut (Arachis hypogaea L.)

Abstract: The linkage map for the recombinant inbred line (RIL) mapping population derived from late leaf spot (LLS) and rust disease susceptible (TAG 24) and resistant (GPBD 4) varieties of peanut was improved by adding 139 new SSR and transposable element (TE) markers. The improved map now has 289 mapped loci with a total map distance of 1730.8 cM and average inter-marker distance of 6.0 cM across 20 linkage groups. Quantitative trait loci (QTL) analysis using improved genetic map with 289 markers and comprehensive ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 21 publications
1
47
0
Order By: Relevance
“…These results indicated that the resistance to LLS in cultivated peanut was controlled by several major QTLs and many minor QTLs, consistent with previous research results [15,46]. When comparing the QTLs for LLS in this study with previous studies (S3 Table) [14,15,46,52,53,54], six major and 10 minor QTLs for LLS in our study were shown to be novel QTLs. This could be due to different genetic backgrounds of the used materials.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicated that the resistance to LLS in cultivated peanut was controlled by several major QTLs and many minor QTLs, consistent with previous research results [15,46]. When comparing the QTLs for LLS in this study with previous studies (S3 Table) [14,15,46,52,53,54], six major and 10 minor QTLs for LLS in our study were shown to be novel QTLs. This could be due to different genetic backgrounds of the used materials.…”
Section: Discussionsupporting
confidence: 92%
“…Due to that genome fragments from wild peanut were transferred into cultivated peanuts, this population therefore had high genetic variation and the map had so many polymorphic markers [29]. In the previous studies of QTL mapping for resistance to LLS, GPBD 4 was usually used as a resistant parent [14,15,53]. The source of resistance of GPBD 4 can be traced back to wild species of A .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, AhTE markers might provide an efficient marker system, like SSR markers (Li et al, 2011;Ren et al, 2014), for genetic and genomic studies in groundnut. Recently, AhTE markers have been successfully employed for trait mapping in groundnut (Shirasawa et al, 2012b;Kolekar et al, 2016). They were also used to identify and clone the gene governing various traits (Lee et al, 2006;Monden et al, 2009;Sato et al, 2013) since the transposable element served as a DNA tag.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the large number and variation for transpositional activity of AhMITE1, AhTE markers show considerably high (27.4%) polymorphism (Shirasawa et al, 2012a;Kolekar et al, 2016). In this study, an effort was made to analyze the population genetic parametersusing AhTE markers among a mutant population and a recombinant inbred line (RIL) population of groundnut to assess the utility of AhTE markers in genetic and genomic studies.…”
Section: Introductionmentioning
confidence: 99%
“…The QTL region on A03 was further resolved to 3.06 Mb (131.60–134.66 Mb) genomic region on the A03 pseudomolecule of A genome (Pandey et al., ), which carried ~25 putative candidate genes associated with LLS and rust resistance. SSR (Sujay et al., ), SNP (Pandey et al., ) and AhTE (Kolekar et al., ) markers linked to the QTL/genes were identified. Some of these markers were validated (Sukruth et al., ; Yeri et al., ) and also used for developing foliar disease‐resistant backcross lines (Pasupuleti, Pandey, Manohar, et al., ; Varshney et al., ; Yeri & Bhat, ).…”
Section: Introductionmentioning
confidence: 99%